2017
DOI: 10.1038/s41467-017-00324-x
|View full text |Cite|
|
Sign up to set email alerts
|

Smac mimetics and oncolytic viruses synergize in driving anticancer T-cell responses through complementary mechanisms

Abstract: Second mitochondrial activator of caspase (Smac)-mimetic compounds and oncolytic viruses were developed to kill cancer cells directly. However, Smac-mimetic compound and oncolytic virus therapies also modulate host immune responses in ways we hypothesized would complement one another in promoting anticancer T-cell immunity. We show that Smac-mimetic compound and oncolytic virus therapies synergize in driving CD8+ T-cell responses toward tumors through distinct activities. Smac-mimetic compound treatment with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 45 publications
1
59
0
Order By: Relevance
“…On the other hand, M2 macrophages are characterized by a high level of scavenger-, mannose- and galactose-type receptors, and they have an important role during allergies and helminth-driven inflammatory reactions [ 5 , 6 ]. The dysregulation of macrophage polarization is implicated in the development of pathologies [ 7 ], such as diabetes [ 8 , 9 ], cancer [ 10 13 ], atherosclerosis [ 14 , 15 ], myocardial infarction [ 16 ], obesity [ 17 ] and asthma [ 18 ]. Thus, there is a growing interest in understanding the balancing of M1/M2 polarization and for the possible therapeutic modulation of M1 and M2.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, M2 macrophages are characterized by a high level of scavenger-, mannose- and galactose-type receptors, and they have an important role during allergies and helminth-driven inflammatory reactions [ 5 , 6 ]. The dysregulation of macrophage polarization is implicated in the development of pathologies [ 7 ], such as diabetes [ 8 , 9 ], cancer [ 10 13 ], atherosclerosis [ 14 , 15 ], myocardial infarction [ 16 ], obesity [ 17 ] and asthma [ 18 ]. Thus, there is a growing interest in understanding the balancing of M1/M2 polarization and for the possible therapeutic modulation of M1 and M2.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from direct cancer kills, it also produces antitumor adaptive immunity; however, repopulation of the TME by MDSCs, TAMs, and Tregs can stifle these responses (3,35,36). SMAC mimetic compounds, known to have radiosensitizing properties (10)(11)(12), can also promote both innate and adaptive immune responses (19,20). Using an LLC-OVA model, we have demonstrated the SMAC mimetic Debio 1143 potentiates proinflammatory cytokine release and the tumor-specific adaptive immune response to ART (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…IAP antagonism also modulates innate and adaptive immunity (15), increasing the activation of antigenpresenting cells (16), cell death in monocytes, maturation of monocyte-derived dendritic cells (17), and T-cell activation (18). One study has demonstrated that the combination of oncolytic viruses and SMAC mimetic compounds robustly activates the innate immune system against cancer cells (19). SMAC mimetics also have proved to synergistically promote antitumor immunity alongside programmed death-1 (PD-1) immune checkpoint inhibitors in multiple mouse tumor models (20).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, SMs have shown impressive and broad activity when combined with oncolytic viruses [91], likely due to the increase in local TNF production as a result of oncolytic cell death. The combination of SMs and oncolytic virus therapy, both of which have significant immunomodulatory properties, can synergise to promote anti-tumour T cell responses due to apoptosis of SM-treated cells triggered by TNF secreted during viral infection [114]. Treatment with the oncolytic virus, M1, through the release of associated PAMPs, results in an increase in inflammatory cytokine secretion via the host innate immune system.…”
Section: Role Of Smac-mimetics In Oncolytic Virus Immunotherapymentioning
confidence: 99%